Pelaksanaan Good Governance Di Kantor Kecamatan Palu Barat - Rika Rika; M. Nur Alamsyah (Jurnal ADMINISTRATOR, 2020)
The implementation of good governance principles to public service in at regent office in west Palu have been done, but the reality it is not optimal yet. There are still many service that is not applying, such as the worker’s discipline which is not run well and the extroverted or the information preparation (transparancy) is so hard to be found and the level of society participation is still low, it is caused by the less motivation of bureaucracy to be a participant in every wisdom. This fenomena is happened generally and become a problematic in government implementation. The implementation of good governance principles at regent office in west palu has been applied but still not maximal like it is hoped. This can be seen be from the cooperation among government, private sector and society which still not run well, this is because certain factors like there is no chance from society to participate due to many activities. And also the lack of human resourcesor the lack of knowledge from officers at regent government this is also because the lack of facilitiesto apply the tasks of government which influence the work from regent officers.